2000
DOI: 10.1106/2ulx-mnqh-y1af-8b5v
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Sensing and Shape Control of Piezoelectric Bimorph Mirrors

Abstract: Meeting the long term needs of the remote sensing community requires the development of large aperture space-based optical systems to achieve dramatic improvements in resolution and sensitivity. It is possible that ultralarge apertures will be obtained using deployable thin film mirror technology, yet many technological barriers must be overcome to make this approach viable. This paper summarizes an initial research effort into the development of piezoelectric thin film mirrors that can be actively shaped usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…To respond to varying operating conditions and external disturbances, the component shape has to change adaptively to maintain optimal system performance and enhance versatility. Various adaptive shape change (shape morphing) systems have been developed and incorporated into practical applications (Austin and Van Nostrand, 1995;Washington, 1996;Austin et al, 1997;Martin et al, 1997Martin et al, , 1998Martin et al, , 2000Yoon and Washington, 1998;Webb et al, 1999;Yoon et al, 2000;Ameduri et al, 2001;Angelino and Washington, 2001). Most of these shape morphing systems involve the use of smart actuators and materials, such as shape memory alloys (SMAs) and lead zirconate titanate (PZT).…”
Section: Shape Change Using Compliant Mechanismsmentioning
confidence: 99%
“…To respond to varying operating conditions and external disturbances, the component shape has to change adaptively to maintain optimal system performance and enhance versatility. Various adaptive shape change (shape morphing) systems have been developed and incorporated into practical applications (Austin and Van Nostrand, 1995;Washington, 1996;Austin et al, 1997;Martin et al, 1997Martin et al, , 1998Martin et al, , 2000Yoon and Washington, 1998;Webb et al, 1999;Yoon et al, 2000;Ameduri et al, 2001;Angelino and Washington, 2001). Most of these shape morphing systems involve the use of smart actuators and materials, such as shape memory alloys (SMAs) and lead zirconate titanate (PZT).…”
Section: Shape Change Using Compliant Mechanismsmentioning
confidence: 99%
“…Examples include plate and shell structures with patches of active materials such as shape memory alloys or piezoelectric ceramics (Wang et al, 1997;Lin and Ren, 1998;Wang and Wang, 2000;Quek et al, 2003;Aldraihem and Khdeir, 2003), piezoelectric thin film mirrors that can be actively shaped using electric fields applied by an electron flux at selected locations (Martin et al, 2000;Martin and Main, 2002), and the post-cured shape of laminated composites (Hyer, 1981). Although these applications do not lie within the scope of this work, the approach that is developed can be readily applied to these and many other related problems.…”
Section: Introductionmentioning
confidence: 99%
“…Here, it was shown that the addition of thin PVDF patches did not significantly alter the modal characteristics of the inflated host structure. Reference [8] investigated a noncontact distributed actuation methodology of PVDF films using a steerable electron beam. Furthermore, [1] explored the performance of electron-beam-actuated electroactive polymers (EAP) for global shape control of the W error.…”
Section: Introductionmentioning
confidence: 99%